THE IDEA OF DELIVERING PASSIVE VOICE AS TEACHING MATERIAL BY USING INTEGRATED STEPS - Firmansyah Diyata (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
Some students tend to face difficulties when they are trying to change active sentences into the passive ones. The difficulties come from several problems, such as the students do not know the parts of the sentence, do not recognize the tense of the sentence, or they are still confused how to apply the form that changes the active sentences into the passive sentences. To help the students with those problems, arranging integrated steps that show them how to change the active voice into the passive ones are considered to be a good idea. The integrated steps in this case are started by dividing the parts of the sentence that helps the students to know which subject, predicate and the object of that sentence. Then the students will place the object of the sentence as the subject of the passive sentence. The next step, the student must decide the verb be of the passive sentence by referring the tense of the active sentence and whether the subject of the passive sentence is plural or singular. After that, students change the verb in active sentence into past participle and use it as the verb for passive voice. Then the students can extend the sentence if it is necessary to show the actor in passive sentence by using word ‘by’. Finally, if the sentence is extended, the students use the subject of the active sentence as the object in passive voice. By using the integrated steps is hoped that the students will understand how to change active sentence into the passive ones efficiently.